A Bibliometric Analysis of Review Types Published in the Nursing Scientific Literature. (18th January 2023) - Carter-Templeton, Heather; Wrigley, Jordan; Nicoll, Leslie H.; Owens, Jacqueline K.; Oermann, Marilyn H.; Ledbetter, Leila S.
Abstract : Reviews in the nursing scientific literature have steadily expanded in scope and range. This has resulted in a variety of terms used to describe these reports found in bibliographic databases, creating confusion. This study investigated the status of reviews in the published nursing literature, including: (1) number of reviews; (2) conventions related to naming and description; (3) publication location; and (4) areas of clarity and inconsistency. Eighty-five percent of reviews (n = 5893) included in this study adhered to an identified review strategy, complete with a clear approach. The remainder (n = 981, 15%) did not. Authors of reviews must follow the identified protocol for their review type and share all relevant information including standards and rigor. Editors and peer reviewers need to possess up-to-date knowledge on methodologies associated with specific review types.